Implementation of CI/CD Architecture Based on GitHub Actions and Docker on Low Resource Servers - Agun Guntara; Wildan Fathir Qinthara; Yanyan Sofiyan (FKOM UNIKU, 2026)
Manual application integration and deployment often introduce severe operational bottlenecks, including high human error configuration risks and strict dependency on individual system administrators. This research aims to design and implement an automated Continuous Integration and Continuous Deployment (CI/CD) pipeline architecture utilizing GitHub Actions and Docker containerization for an attendance web application at Puskesmas Cimalaka. Employing a descriptive qualitative method with a case study approach, this study focuses on evaluating the workflow transformation and operational efficiency within a limited, low-resource server environment. The implementation results reveal that the proposed architecture successfully shifts the operational workload from human iterative routines to external cloud runner infrastructures, isolating the intensive environment compilation and monolithic dependency builds away from the target host. In conclusion, this structural deployment framework radically compresses active developer engagement to near zero, heavily mitigates operational risks under rigid hardware boundaries, and provides a highly stable, secure, and easily replicable DevOps deployment blueprint for medium-to-low scale public institutions